Reading Political Integralism Using Eclectic and Dialectic Methods: A Study of Supomo's Reception of Spinoza, Adam Muller, and Hegel - Jegalus, Norbertus - (Institut Filsafat dan Teknologi Kreatif Ledalero, 2024)
Supomo put forward the idea of political integralism (Staatsidee Integralistik), in the Indonesian State Establishment Session (1945), by referring to three Western philosophers: Spinoza, Adam Muller, and Hegel. The question from an academic aspect that has not been answered until now is why integralism must be based on these three philosophers and not others, and also why must it start with Spinoza and end with Hegel and not another arrangement? With this philosophical study method, we want to explore why Supomo mentioned the three philosophers in such an arrangement, was it because of chronological or study method reasons? Therefore, there are two possible answers: First, Supomo took the appropriate elements from each philosopher according to the needs to fill the philosophical substance of his integralistic idea, so it is an eclectic method. Second, considering that the three philosophers cannot simply be connected, let alone equated, and supported by the structure of Supomo's speech which is also dialectical, so he uses the dialectical method. The result of this study is that integralism uses the dialectical method with its central idea of religion: Spinoza (thesis) rejects a religious state; Adam Muller (antithesis) accepts a religious state; and Hegel (synthesis) defines co-existence as both, thus recognizing that religion exists in the state but does not have to be a religious state. Hegel's answer is by the optio fundamentalis of Supomo's politics, namely rejecting the Islamic State demanded by Muslims and wanting to build a nation-state that includes all groups. Keywords: integralistic state, organic state, dialectic, religious state, nation state